Taxes and Capital Structure: Evidence from Firms' Response to the Tax Reform Act of 1986 - Givoly, Dan; Hayn, Carla; Ofer, Aharon R.; Sarig, Oded (Review of Financial Studies, 1992)
[While the theoretical relation between taxes and capital structure has been extensively analyzed, the empirical evidence on this issue has thus far been inconclusive. One of the main difficulties confronting previous empirical studies of the cross-sectional relationship between taxes and leverage was the control of intervening variables. The Tax Reform Act of 1986 (TRA), which drastically changed the tax regime, provides a unique opportunity to assess the interaction between taxes and leverage decisions in a controlled environment. We test the relationship between leverage and certain tax-related variables for a large sample of companies in the years surrounding the enactment of the TRA. The results support the tax-based theories of capital structure. The findings indicate that there exists a substitution effect between debt and nondebt tax shields, and that both corporate and personal tax rates affect leverage decisions.]